2017
DOI: 10.1097/dad.0000000000000635
|View full text |Cite
|
Sign up to set email alerts
|

Marker Protein Expression Combined With Expression Heterogeneity is a Powerful Indicator of Malignancy in Acral Lentiginous Melanomas

Abstract: We show that marker protein expression, when combined with heterogeneous expression as shown by immunohistochemistry, is a powerful indicator of malignancy in ALMs, especially, when protein pairs are combined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Cintra Lopes Carapeto et al [85] performed IHC to assess heterogeneity of marker expression in four different areas within each of 49 acral lentiginous melanoma tumors and 60 compound nevi. The most heterogeneous protein was MYC which was heterogeneous in 75% of tumors.…”
Section: Intratumor Heterogeneity In Melanomamentioning
confidence: 99%
See 1 more Smart Citation
“…Cintra Lopes Carapeto et al [85] performed IHC to assess heterogeneity of marker expression in four different areas within each of 49 acral lentiginous melanoma tumors and 60 compound nevi. The most heterogeneous protein was MYC which was heterogeneous in 75% of tumors.…”
Section: Intratumor Heterogeneity In Melanomamentioning
confidence: 99%
“…Association between tumor heterogeneity and cancer progression as well as prognosis is poorly explored in melanoma. However, it was shown that heterogeneity of protein marker expression is a more powerful indicator of malignancy in acral lentiginous melanomas than protein marker expression alone [85] . Nonetheless, further studies are necessary.…”
Section: Implications For Diagnosis and Treatmentmentioning
confidence: 99%